2022
DOI: 10.1136/bmjopen-2022-061062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how patients’ pain beliefs influence chronic low back pain management in Ghana: a grounded theory approach

Abstract: IntroductionChronic low back pain (CLBP) is associated with negative consequences in high and low/middle-income countries. Pain beliefs are important psychosocial factors that affect the occurrence and progression of CLBP and may be influenced by the sociocultural context and interactions with healthcare professionals (HCPs). The pain beliefs of Ghanaian patients with CLBP are unknown and the factors influencing pain beliefs in African contexts are unclear.ObjectivesTo explore the pain beliefs of Ghanaian pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
(195 reference statements)
0
7
0
Order By: Relevance
“…The socio‐cultural beliefs about chronic musculoskeletal pain, such as low back pain, influence the health‐seeking behaviours of the population (Ampiah et al., 2022). Bhutan is also known as ‘the land of medicinal herbs,’ and remedies made from herbs and minerals plays an important role in Bhutanese society.…”
Section: Discussionmentioning
confidence: 99%
“…The socio‐cultural beliefs about chronic musculoskeletal pain, such as low back pain, influence the health‐seeking behaviours of the population (Ampiah et al., 2022). Bhutan is also known as ‘the land of medicinal herbs,’ and remedies made from herbs and minerals plays an important role in Bhutanese society.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cultural beliefs and attitudes that are not directly related to religion can act as confounding factors. For example, a study of Ghanaian adults revealed that their religion was a source of hope and support in the face of chronic back pain; on the other hand, many of these adults had culturally-derived maladaptive beliefs related to pain, which were not specifically related to their religion ( 56 ). Similar results regarding the positive role of religion were reported in a study of Spanish and Brazilian patients with back pain ( 57 ).…”
Section: Introductionmentioning
confidence: 99%
“…This fosters holistic understanding of the impact of CLBP and highlights important indicators to be considered in the management of CLBP 12. Conversely, a qualitative study18 and review19 on management practices for LBP in Ghana and African countries suggest the predominance of biomedical and passive strategies (eg, electrotherapy, massage, prolonged pain medication use), and an absence of biopsychosocial strategies. However, exercises are commonly prescribed by Ghanaian physiotherapists 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, exercises are commonly prescribed by Ghanaian physiotherapists 8. Late health seeking and the use of herbal medication for CLBP in Ghana have also been reported by Ghanaian patients experiencing CLBP 18. CLBP is a long-term and complex condition that may persist beyond tissue healing 20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation